The Effect Of Training Using Hand Paddle And Fins On Craw Style Swimming Speed At Ulma Swimming Club - Harion Harion; Lina Tri Astuty; Martiani Martiani (Journal of Physical Education and Sports, 2026)
This study aims to determine the Effect of Training Using Hand Paddle and Fins on Craw Style Swimming Speed ​​at the ULMA Swimming Club. This type of research is quantitative research. The research sample was 20 people. The instrument used in this study was a craw style swimming speed test using the Hand Paddle and Fins training method. Where the results of the study can be seen an increase from the initial pretest to the posttest. This can be seen from the figures obtained from the results of the study where for the pretest value as many as 10 people (50%) have a less category and for the posttest as many as 12 people (60%) have a sufficient category, meaning that the results of the study can be said to have experienced a significant increase.